Pendampingan Guru Inovatif dan Reflektif dalam Melakukan Analisis Pembelajaran dengan Transcript Based Lesson Analysis (TBLA) - Sri Hastuti Noer; Pentatito Gunowibowo; Mella Triana; Santy Setiawati (Nuwo Abdimas, 2023)
Facing technology's rapid development, teachers must continue to learn and innovate. Teachers must be able to lead, innovate and make changes to develop the quality of their schools. On an independent initiative, a teacher can make himself a reflective and innovative teacher. One of the efforts that can be made is through mentoring activities in conducting learning analysis with TBLA. To reflect on learning, the teacher must first understand the principles of reflection, analyze the reflection results and interpret them. The analysis of respondents from mathematics teachers in Lampung Province (February-March 2022) revealed that teachers' understanding of learning reflection and its benefits was still low. Therefore, mentoring activities in learning analysis with TBLA for mathematics teachers were carried out. Based on the implementation results, the service activities showed an increase in the understanding and skills of the participating teachers regarding the analysis of learning reflection with TBLA. This is indicated by the significant average score of the n-gain theory of 0.41 (medium improvement category). One teacher from 15 participating teachers has carried out practice/assistance as an example of its application. However, the practice carried out by model teachers is the first step in creating reflective and innovative teachers. Teachers who can analyze situations in the learning process can open up problems during learning so that teachers get input for improving their learning. Therefore, increasing the knowledge and skills of the participating teachers regarding analysis and reflection of learning with TBLA has to be improved even more.